The Relationship Between Inflammation and Post-traumatic Stress Disorder - Sun, Yajing; Qu, Yuanyuan; Zhu, Jianwei (Frontiers in Psychiatry, 2021)
Background: Stress disorders, such as post-traumatic stress disorder (PTSD), are attracting much attention. However, the relationship between traumatic stress and inflammation is rarely discussed. Subjects and Methods: As studies have linked PTSD to altered susceptibility to various diseases, such a psychiatric condition may lead to long-term systematic changes in physiological functions. We searched PubMed with the keywords “traumatic stress”, “stress disorders”,“post-traumatic stress disorder” and “inflammation”. Results: Based on 66 previously published studies, we reviewed the long-term effects of PTSD, as well as traumatic events, on inflammatory function from both epidemiological and biological perspectives. PTSD is related to the immune response, including an increase in inflammatory factors and a reduction in anti-inflammatory factors. Additionally, it has been demonstrated that traumatic stress disorder and immune disease share a common genetic basis at the gene expression level. Conclusions: Understanding this relationship is of great significance for optimizing treatment plans for patients with PTSD.